Listening to health workers: lessons from Eastern Uganda for strengthening the programme for the prevention of mother-to-child transmission of HIV - Rujumba Joseph; Tumwine James K; Tylleskär Thorkild; Neema Stella; Heggenhougen Harald K (BMC, 2012)
Abstract Background The implementation and utilization of programmes for the prevention of mother-to-child transmission (PMTCT) of HIV in most low income countries has been described as sub-optimal. As planners and service providers, the views of health workers are important in generating priorities to improve the effectiveness of the PMTCT programme in Uganda. We explored the lessons learnt by health workers involved in the provision of PMTCT services in eastern Uganda to better understand what more needs to be done to strengthen the PMTCT programme. Methods A qualitative study was conducted at Mbale Regional Referral Hospital, The AIDS Support Organisation (TASO) Mbale and at eight neighbouring health centres in eastern Uganda, between January and May 2010. Data were collected through 24 individual interviews with the health workers involved in the PMTCT programme and four key informants (2 district officials and 2 officials from TASO). Data were analyzed using the content thematic approach. Study themes and sub-themes were identified following multiple reading of interview transcripts. Relevant quotations have been used in the presentation of study findings. Results The key lessons for programme improvement were: ensuring constant availability of critical PMTCT supplies, such as HIV testing kits, antiretroviral drugs (ARVs) for mothers and their babies, regular in-service training of health workers to keep them abreast with the rapidly changing knowledge and guidelines for PMTCT, ensuring that lower level health centres provide maternity services and ARVs for women in the PMTCT programme and provision of adequate facilities for effective follow-up and support for mothers. Conclusions The voices of health workers in this study revealed that it is imperative for government, civil society organizations and donors that the PMTCT programme addresses the challenges of shortage of critical PMTCT supplies, continuous health worker training and follow-up and support for mothers as urgent needs to strengthen the PMTCT programme.